Acute subclavian steal syndrome following blunt thoracic trauma. Issue 4 (July 1972) - Blesovsky, A.; Colanceski, V.; Ferguson, J.; Urquhart, W.
Abstract : A rare case of acute subclavian steal syndrome following blunt thoracic trauma is described. By aortography, obstruction of the origin of the left subclavian artery was found and the reversed flow through the vertebral artery was demonstrated. This injury was successfully treated by an aortosubclavian bypass Dacron prosthesis using a left posterolateral thoracotomy approach.